2007
DOI: 10.1128/jcm.00986-06
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Antimicrobial Susceptibility Testing of Campylobacter spp. by the Agar Dilution and the Agar Disk Diffusion Methods

Abstract: The correlation and the level of agreement between the standardized agar dilution and the agar disk diffusion methods for antimicrobial susceptibility testing of Campylobacter were investigated. A high-level agreement between the two methods was evident for aminoglycosides and fluoroquinolones, while a low-level agreement was observed for other antibiotics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
1
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(78 citation statements)
references
References 19 publications
2
74
1
1
Order By: Relevance
“…In the current study, all isolates were susceptible or moderately susceptible to erythromycin. Unlike some surveillances (20,23,(28)(29)(30)(31)(32)(33)(34), we did not find macrolide-resistant strains.…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, all isolates were susceptible or moderately susceptible to erythromycin. Unlike some surveillances (20,23,(28)(29)(30)(31)(32)(33)(34), we did not find macrolide-resistant strains.…”
Section: Discussioncontrasting
confidence: 99%
“…Susceptibility tests for campylobacter species are not standardized (there is no recommendation by the CLSI), so there are variabilities in the susceptibility reported (Vandenberg et al, 2006). However, we used disk diffusion method for the susceptibility testing of C. jejuni and C. coli strains used in this study followed by determination of MIC of the intermediately resistant and resistant strains by agar dilution method (Luangtongkum et al, 2007). Susceptibility testing of Campylobacter species is important to facilitate appropriate treatment where indicated and also for surveillance of emergence of drug resistance.…”
Section: Resultsmentioning
confidence: 99%
“…All Campylobacter strains were tested against ampicillin (10 ”g), tetracycline (30 ”g), azithromycin (15 ”g), erythromycin (15 ”g), chloramphenicol (30 ”g), gentamicin (10 ”g), nalidixic acid (30 ”g), ciprofloxacin (5 ”g), levofloxacin (5 ”g), ofloxacin (5 ”g), fosfomycin (50 ”g) and sulphamethoxazole-trimethoprim (1.25 ”g) by disk diffusion method as described by Luangtongkum et al (2007) with some modifications. Again, all intermediately resistant and resistant Campylobacter strains confirmed by disk diffusion method except sulphamethoxazole-trimethoprim resistant strains were subjected to the determination of minimum inhibitory concentration (MIC) by agar dilution method as described by Luangtongkum et al (2007) with some modifications.…”
Section: Antimicrobial Agents and Susceptibility Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the seasonality of campylobacteriosis is much debated (10). Several studies have reported good correlations between disc diffusion and agar dilution methods for the drug susceptibility testing of Campylobacter in developed and in developing countries (4, 15,35,36). In developing countries, various patterns of Campylobacter susceptibility to antibiotics were described.…”
Section: Bacteriological Datamentioning
confidence: 99%